2016
DOI: 10.1111/ina.12288
|View full text |Cite
|
Sign up to set email alerts
|

Semi-volatile organic compounds in the air and dust of 30 French schools: a pilot study

Abstract: The contamination of indoor environments with chemical compounds released by materials and furniture, such as semi-volatile organic compounds (SVOCs), is less documented in schools than in dwellings-yet children spend 16% of their time in schools, where they can also be exposed. This study is one of the first to describe the contamination of the air and dust of 90 classrooms from 30 nursery and primary schools by 55 SVOCs, including pesticides, phosphoric esters, musks, polycyclic aromatic hydrocarbons (PAHs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 62 publications
3
34
0
Order By: Relevance
“…One thing noted is that OPFRs concentrations may be underestimated, e.g. desorption of OPFRs from dust particles may occur under the reduced pressure in the vacuum process and fine and ultrafine dust may be missed collecting during the vacuuming [40].…”
Section: Opfrsmentioning
confidence: 99%
“…One thing noted is that OPFRs concentrations may be underestimated, e.g. desorption of OPFRs from dust particles may occur under the reduced pressure in the vacuum process and fine and ultrafine dust may be missed collecting during the vacuuming [40].…”
Section: Opfrsmentioning
confidence: 99%
“…Multiple studies have reported on the concentrations of SVOCs identified in the air and dust of diverse indoor environments . However, limited by analytical capabilities, the majority of published studies only report on small numbers of SVOCs, thus providing restricted insight into the chemical complexity and the total burden encountered in indoor environments.…”
Section: Introductionmentioning
confidence: 99%
“…4,17 Multiple studies have reported on the concentrations of SVOCs identified in the air and dust of diverse indoor environments. 3,9,[18][19][20][21][22][23][24][25] However, limited by analytical capabilities, the majority of published studies only report on small numbers of SVOCs, thus providing restricted insight into the chemical complexity and the total burden encountered in indoor environments. Historically, methods for analyzing SVOCs in both outdoor and indoor environments have relied on long time scale (days to weeks) collection of particulate matter and gases on filters and sorbents followed by offline analysis in the laboratory.…”
mentioning
confidence: 99%
“…[1,3]. Their presence in indoor environment is a matter of concern because many of these SVOCs are suspected of being toxic and/or endocrine disruptors, with effects on the reproductive tract development, the thyroid function, the nervous system and the development of metabolic diseases such as obesity and diabetes [3][4][5][6]. In indoor environments, human exposure to SVOCs occurs through different pathways including air inhalation, ingestion of settled dust and dermal contact with surfaces, indoor air and settled dust.…”
Section: Introductionmentioning
confidence: 99%